Assessment of a 72-hour repeated exposure to Swedish snus extract and total particulate matter from 3R4F cigarette smoke on gingival organotypic cultures. (March 2019) - Zanetti, Filippo; Sewer, Alain; Titz, Bjoern; Schlage, Walter K.; Iskandar, Anita R.; Kondylis, Athanasios; Leroy, Patrice; Guedj, Emmanuel; Trivedi, Keyur; Elamin, Ashraf; Martin, Florian; Frentzel, Stefan; et al.
Abstract: Swedish snus is a smokeless tobacco product that contains reduced levels of harmful compounds compared with cigarette smoke. In Sweden, where snus use exceeds smoking among men, relatively low rates of major smoking-related diseases have been recorded. To better understand how snus use could align with current tobacco harm reduction strategies, its potential mechanisms of toxicity must be investigated. This study aimed to determine, via a systems toxicology approach, the biological impact of repeated 72-hour exposure of human gingival epithelial organotypic cultures to extracts from both a commercial and a reference snus and the total particulate matter (TPM) from cigarette smoke. At concentrations relevant for human use, cultures treated with snus extracts induced mild, generally reversible biological changes, while TPM treatment induced substantial morphological and inflammatory alterations. Network enrichment analysis and integrative analysis of the global mRNA and miRNA expression profiles indicated a limited and mostly transient impact of the snus extracts, in particular on xenobiotic metabolism, while the effects of TPM were marked and sustained over time. High-confidence miRNAs that might be related to pathological conditions in vivo were identified. This study highlights the limited biological impact of Swedish snus extract on human organotypic gingival cultures. Graphical abstract: Image 1 Highlights: A systems toxicology approach was used for the first time to assess the biological impact of Swedish snus in vitro . Culture morphology was minimally affected by exposure to snus. High-confidence miRNAs associated with exposures to snus or cigarette smoke total particulate matter were identified. The alterations observed in the gene expression networks in response to snus exposure tended to revert with time. The xenobiotic metabolism process was differentially impacted by Swedish snus and cigarette smoke total particulate matter.